Community survey of factors associated with consultation for low back pain. Issue 7172 (5th December 1998) - Waxman, Robin; Tennant, Alan; Helliwell, Philip
Abstract : Objective: To investigate the psychosocial factors associated with consultation for low back pain. Design: Two phase cross sectional postal survey. Setting: Bradford Metropolitan Health District. Subjects: 1813 adults responding to the phase 1 questionnaire. 540 of the 782 with an episode of low back pain in the past 12 months completed the second questionnaire. Main outcome measures: Six psychosocial constructs. Results: 406 (52%) of the respondents reporting back pain in the past 12 months had not consulted a health professional. Logistic regression showed that consultation was associated with externalised beliefs regarding pain management (odds ratio 3.6; 95% confidence interval 2.1 to 6.0). Duration of pain affected the factors associated with consultation. Consultation for episodes lasting less than two weeks (n=290) was associated with greater than median pain (3.0; 1.7 to 5.5), consultation for episodes over two weeks (n=243) was associated with increased disability (3.7; 1.5 to 9.0), and consultation for episodes over three months (n=143) with increased depression (3.9; 1.3 to 11.8). Conclusions: The results support a role for psychosocial factors in consultation for low back pain and suggest that the reasons for consultation vary with duration of pain. Duration of the episode may be a useful guide to management of non-specific low back pain.